2016
DOI: 10.1111/tan.12933
|View full text |Cite
|
Sign up to set email alerts
|

The HLA‐A, ‐B and ‐DRB1 polymorphism in a large dataset of South Brazil bone marrow donors from Rio Grande do Sul

Abstract: Human leukocyte antigen (HLA) genes are very informative in population genetics studies and their variability has been widely used to reconstruct the history of geographic and/or demographic expansions of human populations. The characterization of HLA diversity at the population level is also fundamental in clinical studies, particularly for bone marrow transplantation programs. In this study, we investigated the HLA molecular variation in Rio Grande do Sul, South Brazil, in order to identify possible regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(48 reference statements)
2
7
0
Order By: Relevance
“…In addition, these data may improve donor‐recipient matching, as an increasing number of studies show that HLA genes other than the most studied HLA‐A , ‐B , ‐C , ‐DQB1 , and ‐DRB1 also impact hematopoietic stem cell and organ transplantation . Our results reinforce allelic and haplotypic similarities between the population from Curitiba and European populations, which corroborates previous studies that analyzed Euro‐descendants from Southern Brazil …”
Section: Discussionsupporting
confidence: 90%
“…In addition, these data may improve donor‐recipient matching, as an increasing number of studies show that HLA genes other than the most studied HLA‐A , ‐B , ‐C , ‐DQB1 , and ‐DRB1 also impact hematopoietic stem cell and organ transplantation . Our results reinforce allelic and haplotypic similarities between the population from Curitiba and European populations, which corroborates previous studies that analyzed Euro‐descendants from Southern Brazil …”
Section: Discussionsupporting
confidence: 90%
“…We found that HLA itself is a better predictor of ancestry than the self‐declaration based on skin color, corroborating findings from other studies with other genetic markers . In 2017, in an extensive study using more than 97 000 voluntary bone marrow donors across the state, we tested whether there was population structure according to the state's political division . The results indicated that there is no population structure according to this division, but there is genetic (HLA) structure reflecting the cultural regions associated to the colonization history of Rio Grande do Sul .…”
Section: Bone Marrow Donors and Other Studies In Urban Populationssupporting
confidence: 84%
“…For a broader view of the HLA in Brazilian populations we gathered data from all studies that presented allele frequencies genotyped by molecular methods for HLA-A, HLA-B and HLA-DRB1 included in this revision and we calculated the Prevosti's genetic distance as described elsewhere. 43 Studies based on patients with autoimmune diseases were not included to avoid bias. The allele frequencies used were at first field level (low resolution) and the results were plotted in multidimensional scaling (MDS) (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations